2009
DOI: 10.1007/s12011-009-8559-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Elements of Human Anterior Commissure and Olfactory Bulb and Tract

Abstract: To examine whether there were gender differences in the various brain regions, the authors investigated the gender differences in seven element contents of the anterior commissure, mammillary body, and olfactory bulb and tract by direct chemical analysis. After ordinary dissection at Nara Medical University was finished, the anterior commissures, mammillary bodies, and olfactory bulbs and tracts were resected from the cerebra cut at median line. The brain samples were treated with 99.5% ethanol three times to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The findings from the current investigation therefore highlight the similarities in olfactory bulb and tract metal concentrations between humans and rodents, and confirm the reproducibility of ICP-MS as a technique. However, although the current study aligns closely with these previous studies, which were all performed on unfixed tissue, results were markedly different in two other studies that used chemically fixed olfactory bulbs and tracts from cadavers that had previously been used for medical student teaching 56 , 57 . The combination of these results underscore the importance of tissue preparation, as ICP-MS is very susceptible to contamination 58 60 .…”
Section: Discussionsupporting
confidence: 62%
“…The findings from the current investigation therefore highlight the similarities in olfactory bulb and tract metal concentrations between humans and rodents, and confirm the reproducibility of ICP-MS as a technique. However, although the current study aligns closely with these previous studies, which were all performed on unfixed tissue, results were markedly different in two other studies that used chemically fixed olfactory bulbs and tracts from cadavers that had previously been used for medical student teaching 56 , 57 . The combination of these results underscore the importance of tissue preparation, as ICP-MS is very susceptible to contamination 58 60 .…”
Section: Discussionsupporting
confidence: 62%
“…The authors [43] previously found the gender differences in the Zn content of the anterior commissure and in the Ca, P, and Zn contents of the olfactory bulb and tract. The Zn content of the anterior commissure and olfactory bulb and tract was significantly higher in men than in women.…”
Section: Discussionmentioning
confidence: 96%
“…A few studies exists regarding gender-related differences on some trace element levels, namely Fe, in human brain [27,39,40] but studies concerning Ca and Mg are rather scarce. Some authors [41] consider two different type of gender-related differences in the elements levels of brain regions. The first one corresponds to a difference that was already present in the adulthood and persists up to the old age.…”
Section: Gender-related Differences On Ca and Mg Levels And Smoking Hmentioning
confidence: 99%